1999
DOI: 10.1002/mpr.55
|View full text |Cite
|
Sign up to set email alerts
|

Improving accuracy of major depression age‐of‐onset reports in the US National Comorbidity Survey

Abstract: The current report discusses only one aspect of the information-retrieval process: the recollection of age of onset of psychiatric disorders in epidemiological surveys. Age-of-onset information is often collected in clinical interviews as part of the history-taking process and is used along with other retrospective information about course and family history to build up an initial understanding of the nature of the disorder being treated. Exact dating is generally not critical here, although it is useful to kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

9
1

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 29 publications
1
167
0
1
Order By: Relevance
“…Age of onset was set at the upper end of the bound (e.g., age 12 for respondents who reported that onset was before they became teenagers). Experimental research shows this question sequence yields responses with a much more plausible age of onset distribution than the standard CIDI age of onset question (Knauper et al, 1999).…”
Section: Methodsmentioning
confidence: 96%
“…Age of onset was set at the upper end of the bound (e.g., age 12 for respondents who reported that onset was before they became teenagers). Experimental research shows this question sequence yields responses with a much more plausible age of onset distribution than the standard CIDI age of onset question (Knauper et al, 1999).…”
Section: Methodsmentioning
confidence: 96%
“…Age of onset was set at the upper end of the bound (e.g., age 12 for respondents who reported that onset was before they became teenagers). Experimental research shows that this question sequence yields responses with a much more plausible age of onset distribution than the standard CIDI age of onset question (Knauper et al, 1999).…”
Section: Methodsmentioning
confidence: 96%
“…Second, the temporal order of disorders was determined from retrospective age-of-onset reports. While we used a probing strategy that has been shown to improve recall of age of onset (Knauper et al, 1999), there were doubtlessly residual errors, perhaps especially when distinguishing GAD from disorders with overlapping symptoms. To help mitigate this concern, we performed sensitivity analyses within subsamples reporting an onset of GAD at least five years before the comorbid disorder.…”
Section: Discussionmentioning
confidence: 99%